Layer-by-layer assembly of polyoxometalate–pyrene-decorated fluorescent microspheres for the suspension immunoassay of Listeria monocytogenes. Issue 24 (8th June 2016) - Ju, Wen; Song, Xiuling; Yan, Gang; Xu, Kun; Wang, Juan; Yin, Dehui; Li, Li; Qu, Xiaofeng; Li, Yangguang; Li, Juan
Abstract : A new class of polyoxometalate–pyrene-decorated fluorescent microspheres prepared by a layer-by-layer self-assembly method were used in the suspension immunoassay technique to detect Listeria monocytogenes . Abstract : A fluorescence microsphere suspension array technique has been developed as a promising tool for the molecular detection of Listeria monocytogene ( LM ), which is a dangerous food borne pathogen that can cause severe food intoxication in both humans and animals. In such a technique, fluorescent microspheres as the key matrix for detection are often decorated with neutral organic dyes, which usually suffer from instability, easy photobleaching and loss from the matrix. Herein, we design and synthesize a new organic–inorganic hybrid POM–pyrene compound [N(C4 H9 )4 ]2 [V6 O13 (OCH2 )3 CNH–CH2 –C16 H9 2 ] (1 ), which is employed as a negatively-charged fluorescent material to prepare a new class of fluorescent microspheres by a layer-by-layer electrostatic self-assembly method. As a result, such POM–pyrene-decorated fluorescent microspheres possess obvious luminescence properties, superior photo-stability and long-term stability. Therefore, the POM–pyrene-decorated fluorescent microspheres are conjugated by monoclonal anti- LM antibodies, and introduced into the fluorescence microsphere-based suspension immunoassay system for the detection of LM in food, which exhibits a high sensitivity. The lowest limit of detection (LOD) of LM in artificially contaminated meat is down to 6 CFU g −1 without cross-reactivity with other pathogens. Furthermore, the suspension immunoassay based on PS@POM–pyrene microspheres shows excellent specificity to LM, good repeatability and high efficiency in contrast to the conventional culture-based method.